Medicinal plants used for hypertension treatment by folk healers in Songkhla province, Thailand. (25th March 2018) - Neamsuvan, Oratai; Komonhiran, Panadda; Boonming, Kamonvadee
Abstract: Ethnopharmacological relevance: Hypertension is the most dominant risk factor for the development of cardiovascular, kidney, and eye diseases. In Thailand, illness and hospitalisation in the modern public health system due to high blood pressure is increasing. However, some Thai people have turned their attention to the use of herbal medicines for healthcare. Therefore, this study aimed (1) to study the folk knowledge of hypertension treatment and (2) to study plant utilisation in the treatment of high blood pressure by Songkhla folk healers. Materials and methods: Field surveys and semi-structured interviews about theories of disease, principles of healing, and herbal usage (plant species, parts used, preparation, and application methods) were gathered. The data were analysed by descriptive statistics. The literatures regarding medicinal plants used in any traditional medicine, antihypertension activity, and toxicity was reviewed. Results: Most healers believed that hypertension was caused by the disorder of fire and wind elements in the body. The medicinal plants containing hot and mild tastes, which had the potential for treating problems in the wind element, were applied. A total of 62 species were used for hypertension treatment. Most plants were in the Asteraceae, Piperaceae, Rutaceae, or Zingiberaceae family (4 species each). Herbal medicines were preferred to be prepared by boiling (78%) and consumed by drinking 1 teacup before 3 meals each day (26%). Piper retrofractum and Cleome viscosa had the greatest Frequency of Citation (FC = 6, n = 14). Thirty-seven species have been reported for use in traditional medicine. Twenty-four and 46 species have already been investigated for antihypertension activity and toxicity, respectively. Conclusion: Identifying medicinal plants that have been tested by experienced folk doctors would provide an opportunity for people to choose and consume local herbs that are easy to access in their local area. However, the remaining plants that have not been studied for antihypertension activity and toxicity should be further analysed to confirm their efficacy. Graphical abstract: